Characterization of rattan waste for binderless particleboard (BPB) production - T., Maisarah; Ahmad, Zuraida; A., Roszalia; M.A, Luqman (Trans Tech Publications Ltd., Switzerland, 2015)
The manufacturing of furniture using rattan is becoming common nowadays, and creates high amount of waste that can be value-added into binderless particleboards (BPB). In order to determine the suitability of the rattan waste for production of BPB, characterization of rattan waste is executed and reported in this paper. The physical properties such as density and moisture content of the rattan waste, together with its morphological study and thermal analysis as well as lignin content are evaluated. It is observed that density and moisture content for rattan waste are in the range of 0.64g/cm3, and 11.3% respectively. On the other hand, the morphology of rattan stem showed that rattan waste has various diameters of vascular bundles along with wide metaxylem vessels as well as thin-walled fibres. Thermal analysis of rattan waste explicated that rattan waste went through endothermic process with peak melting point of 177.80˚C during heating. The greatest weight loss occurred at 257.03˚C. Rattan waste has high lignin content of 21.2% that obtained through Klason lignin test. These promising preliminary results show that the rattan waste is appropriate to be used as raw materials in producing BPB.